EGR1 recruits TET1 to shape the brain methylome during development and upon neuronal activity - Zhixiong Sun (Nature Portfolio, 2019)
It is unclear why neuronal activity induced methylation changes are limited to specific loci in the genome. Here, authors show that the DNA demethylation enzyme, TET1, gains its specificity via the interaction with EGR1, a sequence specific DNA binding protein.